Treatment of Cervical Root Perforation Using MTA - case report (Research, Society and Development, 2022)
Introduction: Root perforation is an accident characterized by the communication between the pulp space or root canal with the periodontal tissues that support the dental element. This type of complication can happen due to extensive caries, root resorption or even due to the incorrect use of burs and other endodontic instruments. The present study aimed to report a clinical case in which the endodontic treatment of a dental element with root perforation was performed, using MTA to seal the perforation. Case report: Male patient, 29 years old, was referred to the specialization clinic for continuation and endodontic treatment. The radiographic examination showed thickening of the periodontal ligament space in the apical region and a radiolucent area in the coronary region suggestive of root perforation, clinically confirmed with the use of an electronic foraminal locator. In the first session, chemical-surgical preparation and use of intracanal medication were performed. In the following session, the root perforation was closed with the use of gray MTA, followed by the filling of the canal. Final considerations: Appropriate clinical management, with the use of technology and equipment that aid in the diagnosis, as well as the use of the most suitable materials for the treatment of root perforations, are essential to obtain favorable clinical results.